Atratores para sistemas dinâmicos e suas relações - Carvalho, Quézia Cristiane de Oliveira Maia (2022)
The present work deals with the theory of dynamical systems, approaching the autonomous case (semigroup) and the non-autonomous case (evolution process), with a detailed study of its attractors. We present results that guarantee the existence of the attractor for the semigroups and for the nonautonomous dynamics systems. In this second case, we study the evolution processes and the cocycles, through pullbak and forward dynamics. In addition, we present some results relating the different types of attractors.